The Role of Smoking Status on the Progression-Free Survival of Non-Small Cell Lung Cancer Patients Harboring Activating Epidermal Growth Factor Receptor (EGFR) Mutations Receiving First-Line EGFR Tyrosine Kinase Inhibitor Versus Platinum Doublet Chemotherapy: A Meta-Analysis of Prospective Randomized Trials. (5th February 2015) - Hasegawa, Yoshikazu; Ando, Masahiko; Maemondo, Makoto; Yamamoto, Satomi; Isa, Shun-ichi; Saka, Hideo; Kubo, Akihito; Kawaguchi, Tomoya; Takada, Minoru; Rosell, Rafael; Kurata, Takayasu; Ou, Sai-Hong Ignatius
Abstract: Background: Univariate analyses from several randomized phase III trials seemed to suggest ever-smokers with advanced mutated epidermal growth factor receptor ( EGFRm ) non-small cell lung cancer (NSCLC) did not seem to benefit from EGFR tyrosine kinase inhibitors (TKIs) as first-line treatment when compared with platinum-doublet chemotherapy as measured by progression-free survival (PFS). Methods: A literature-based meta-analysis of PFS outcomes as measured by log-transformed pooled hazard ratio (HR) was performed using a random-effect model. Pooled HRs for smoking status, age, gender, ethnicity, type of EGFR mutation, and EGFR TKI were obtained. Comparison of the pooled HR was performed by metaregression analysis. Results: Among the 1, 649 EGFRm NSCLC patients analyzed from 7 prospective randomized trials (WJTOG3405, NEJ002, EURTAC, OPTIMAL, LUX Lung-3, LUX Lung-6, and ENSURE), 83.7% were Asians, and 30.0% were ever-smokers. An equal percentage of ever-smokers received doublet chemotherapy (30.2%) or EGFR TKI (30.0%). The pooled HR for PFS was 0.29 (95% confidence interval [CI]: 0.21–0.39) for never-smokers and 0.54 (95% CI: 0.38–0.76) for ever-smokers ( p < .007 by metaregression). The pooled PFS HR for exon 19 deletion was 0.25 (95% CI: 0.19–0.31) and 0.44 for exon 21 substitution (95% CI: 0.34–0.57) ( p < .001 by metaregression analysis). The pooled PFS HR was 0.33 (95% CI: 0.24–0.46) for Asians and 0.48 for non-Asians (95% CI: 0.28–0.84) ( p = .261 by metaregression analysis). Conclusion: EGFRm NSCLC patients derived significant PFS benefit from TKI over platinum-doublet chemotherapy as first-line treatment regardless of smoking status; however, PFS benefit is significantly better in never-smokers by metaregression analysis. Abstract : This meta-analysis was carried out to ascertain the role of smoking status in influencing progression-free survival (PFS) outcomes in patients with the two common activating epidermal growth factor receptor mutations ( EGFRm ) who received first-line EGFR tyrosine kinase inhibitors (TKIs) in comparison with platinum-doublet chemotherapy. EGFRm non-small-cell lung cancer patients derived significant PFS benefit from TKI over platinum-doublet chemotherapy regardless of smoking status; however, PFS benefit is significantly better in never smokers by metaregression analysis.